IMF Survey, Volume 35, Issue 18. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
Annual Meetings overview; IMFC communique; World Economic Outlook, chapters I, II, IV; Regional Economic Outlooks: Asia, Africa, Latin America; Low-income countries, high oil prices; Annual Meetings seminar program; Per Jacobsson lecture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet